The Exemplary Personality of the Prophet in Shaping Inclusive Attitudes and Harmony in Educational Institutions - Nurfida, Aminah; Hakim, M Abdul Rahman; Sahir, Ahmad Waffa Kamal (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This article discusses the importance of emulating the personality of Prophet Muhammad (PBUH) in shaping inclusive attitudes and harmony in educational institutions. His personality, which is rich in inclusiveness, compassion, and respect for diversity, serves as a strong foundation for creating an inclusive and harmonious learning environment. By integrating these values into teaching and curricula, educational institutions are expected to strengthen mutual respect, solidarity, and reduce potential conflicts among students. By emulating the principles in the Charter of Madinah and hadiths emphasizing equality and justice, students are encouraged to practice open and empathetic attitudes, which not only enrich social interactions at school but also prepare them to live peacefully in a diverse society. This study affirms that character education based on the example of Prophet Muhammad (PBUH) plays a significant role in shaping a tolerant, broad-minded, and compassionate generation. This education also serves as an important strategy for educational institutions in facing the increasingly complex and multicultural challenges of globalization. The author recommends further research to explore effective teaching methods and comparative studies with educational approaches from other traditions to broaden the implementation of these values. Additionally, evaluating the long-term impact of education based on the personality of Prophet Muhammad (PBUH) in various multicultural contexts can make a meaningful contribution to the development of character education models that are relevant to the challenges of the modern era.